Custom Milled Zirconia Implant Supporting an Ceramic Zirconia Restoration: A Clinical Report - Nair, A; Prithviraj, DR; Regish, KM; Prithvi, S (Kathmandu University Medical Journal, 2015)
Dental implants constitute a well-established approach for replacement of lost teeth with titanium being the most favored material for implantation. However, titanium has its limitations in esthetically demanding cases and neither the form nor material of such implants has changed much over the past 40 years. Today, there is scientific evidence that zirconia dental implants osseointegrate well and offer many advantages over titanium implants. This report demonstrates the successful clinical use of a custom milled root analogue zirconia implant for single tooth replacement. A left maxillary first molar was removed, allowed to heal for four months and a custom-made, root-analogue, roughened zirconia was fabricated and placed. Subsequently it was restored with zirconia all ceramic crown. No complications occurred during the healing period. This successful case warrants further clinical research on zirconia custom milled implants in well controlled trials. Kathmandu Univ Med J 2013; 11(4): 328-331